Optimizing soybean yield in Gandaki Province, Nepal through adjusted sowing dates to avoid early rainfall - Acharya, Ramesh; Kunwar, Saroj; Adhikari, Bhawana (Journal of Agriculture and Natural Resources, 2025)
Soybean yield in high-rainfall regions of western Nepal is highly variable due to interactions among genotype, environment, and management (G×E×M). This study aimed to evaluate soybean genotypes under adjusted sowing dates to enhance yield and reduce the impact of early pre-monsoon rainfall. A two-year field experiment (2020–2021) was conducted at the Directorate of Agricultural Research, Lumle, Kaski, using a randomized complete block design with three replications. Based on first-year observations, sowing was advanced by 15 days in the second year to avoid early rainfall that compromises crop establishment. Significant variation among genotypes was observed for days to 50% flowering, number of branches per plant, number of pods per plant, plant height, and adjusted grain yield. LS-77-16-16 produced the highest pooled yield (1.83 t/ha), while 500-kernel weight, seeds per pod, and plant population per plot were not significantly different. Unlike past reports of up to 96% yield loss when rainfall coincided with flowering to pod-setting, our results indicate that maintaining crop stand under early rainfall is the primary challenge. These findings suggest that early sowing, combined with selection of suitable genotypes, can improve soybean yield stability under variable rainfall conditions.